Creation, Validation, and Use of Photo-Based Smartphone Application for Dietary Fiber Counting Among University Students - Israa, Sharif; Badrasawi, Manal; Zidan, Souzan; Zghier, Hana; Abu Sunaina, Raghad; Abu Mazer, Tamara (Topics in Clinical Nutrition, 2024)
The main aim of this study was to develop a smartphone application specializing in assessing dietary fiber intake of university students. The validity of the application was tested among 45 volunteers, their daily intake was recorded for 3 days using the Daily Fiber application, and intakes were compared with a 3-day food record matched to the same days. The mean intake of dietary fiber using the 3-day food record and our application was 10.08 ± 4.48 and 10.21 ± 4.64 g/d, respectively (P < .01). Overall, Daily Fiber is a promising tool for assessing dietary fiber intake among undergraduates.
Keywords: dietary fiber, smartphone; nutritional assessment; application; undergraduates.